Theraneis vittata Spinola, 1837 (Hemiptera: Heteroptera: Largidae): first record from Argentina - Dellapé, Pablo Matías (2012)
The present note reports the first record of the genus and species Theraneis vitatta Spinola, 1837 (Hemiptera: Heteroptera: Largidae: Larginae) from Moconá, Misiones province, Argentina. This record brings the number of reported genera from Argentina to five, with a total of 12 species.